William Poole in der modernen Makroökonomik: Exegese des ursprünglichen Beitrags und seiner Fortentwicklungen für die offene Volkswirtschaft - Friedrich L. Sell; Silvio Kermer (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2006)
Given all the evidence supporting Milton Friedman's proposition that inflation is now and everywhere a monetary phenomenon, it seems that we are wrong when we tend to ignore the behaviour of the monetary aggregates at our peril. The total neglect of information about the monetary aggregates in the Taylor rule is possibly a strong signal into that erroneous direction. Moreover, so-called "New Keynesianism" has put forward that there is no more need to treat the money market equilibrium in an "LM-setting". Our paper goes back to William Poole's seminal paper on interest rate and money supply rules and extends his earlier work to the open economy, various types of shocks and to the analysis of cooperative and non-cooperative behaviour of central banks. The results achieved confirm that the inclusion of the money market equilibrium enhances the possibilities to compare the costs and benefits of different monetary policy strategies under cooperative or non-cooperative behaviour.
Keywords: E52; F32; E42; 330; Schockabsorption; Zins- vs. Geldmengenregeln; (Nicht-)Kooperative Geldpolitik bei flexiblen Wechselkursen